2016
DOI: 10.1118/1.4944738
|View full text |Cite
|
Sign up to set email alerts
|

Statistical-learning strategies generate only modestly performing predictive models for urinary symptoms following external beam radiotherapy of the prostate: A comparison of conventional and machine-learning methods

Abstract: Logistic regression and MARS were most likely to be the best-performing strategy for the prediction of urinary symptoms with elastic-net and random forest producing competitive results. The predictive power of the models was modest and endpoint-dependent. New features, including spatial dose maps, may be necessary to achieve better models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 52 publications
0
28
0
Order By: Relevance
“…When looking at the AUC metric alone our results were comparable to values published in other SML based EBRT prediction studies. 13,17,18,27,28 Direct comparison of models is limited, however, because most other studies used toxicity as an endpoint rather than dose tolerance. The exception being Caine et al who also investigated protocol compliance but did not provide AUC or other performance metrics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When looking at the AUC metric alone our results were comparable to values published in other SML based EBRT prediction studies. 13,17,18,27,28 Direct comparison of models is limited, however, because most other studies used toxicity as an endpoint rather than dose tolerance. The exception being Caine et al who also investigated protocol compliance but did not provide AUC or other performance metrics.…”
Section: Discussionmentioning
confidence: 99%
“…Each of these approaches vary in complexity but are commonly used in supervised classification problems such as this and have been published in previous EBRT studies with varying levels of success. 13,17,18 Typically, binary classification with SML models is based on a 50% probability threshold. However, many clinical decisions for a binary outcome are not made at this level.…”
Section: Introductionmentioning
confidence: 99%
“…Many research scientists [89][90][91][92][93][94][95] have investigated the application of ML in radiotherapy treatment response and outcome predictions. Lee et al [89] studied utilizing of Bayesian network ensemble to predict radiation pneumonitis risk for NSCLC patients whom received curative 3D conformal radiotherapy.…”
Section: Treatment Outcomementioning
confidence: 99%
“…The study results indicated that random forest and elastic net logistic regression yield higher discriminative performance in (chemo) radiotherapy outcome and toxicity prediction than other studied classifiers. Yahya et al [93] explored multiple statistical-learning strategies for prediction of urinary symptoms following external beam radiotherapy of the prostate. The study results showed that logistic regression and multivariate adaptive regression splines (MARS) were most likely to be the best-performing strategy for the prediction of urinary symptoms.…”
Section: Treatment Outcomementioning
confidence: 99%
“…Urinary toxicity is a challenging issue, not only due to the variety of associated irritating or obstructive symptoms, but also owing to the limitations of dose descriptors and difficulties identifying the regions at risk responsible for those symptoms [4][5][6]. The bladder, for example, presents the largest inter-fraction shape variations, causing geometric and dose uncertainties that limit the possibility of accurately modeling the dose-volume response concerning GU toxicity [4,7,8,9 ].…”
Section: Introductionmentioning
confidence: 99%